The Rise and the Fall of Betatrophin/ANGPTL8 as an Inducer of β-Cell Proliferation - Mohamed Abu-Farha; Ashraf Al Madhoun; Jehad Abubaker (Journal of Diabetes Research)
Diabetes is a global health problem that is caused by impaired insulin production from pancreatic β-cells. Efforts to regenerate β-cells have been advancing rapidly in the past two decades with progress made towards identifying new agents that induce β-cells regeneration. ANGPTL8, also named betatrophin, has been recently identified as a hormone capable of inducing β-cells proliferation and increasing β-cells mass in rodents. Its discovery has been cherished as a breakthrough and a game changer in the field of β-cells regeneration. Initially, ANGPTL8 has been identified as atypical member of the angiopoietin-like protein family as a regulator of triglyceride in plasma through its interaction with ANGPTL3 and its regulation of lipoprotein lipase activity. In this review, we will review literature on the proposed role of ANGPTL8 in β-cells proliferation, the controversy regarding this role, and the emerging data questioning its involvement in β-cells proliferation. Additionally we will discuss new clinical data that describes its role in diabetes and the putative therapeutic targeting of this protein.